Hydrolysis of Lignocellulosic Biomass for Recovering Hemicellulose: State of the Art - M. Rafiqul, Islam; Mimi Sakinah, A. M.; Zularisam, A. W. (Springer, 2017)
Hemicellulose, a heteropolysaccharide, is a second major component of lignocellulosic biomass (LCB). It is a potential source of various rare sugars, mainly xylose, because the biomass is cheap, renewable, and available globally. Xylose can be an economic and attractive substrate to produce numerous specialty chemicals, especially xylitol. It is particularly significant to depolymerize the complex composition of biomass to recover hemicellulosic sugars and to prepare cellulosic part available for efficient digestion. LCB hydrolysis by various techniques is an inevitable method for depolymerizing hemicellulose into xylose and other hemicellulosic sugars. Among the general methods of hemicellulose hydrolysis (such as acid, autohydrolysis, enzyme, combined acid-enzyme, and autohydrolysis-enzyme), dilute acid hydrolysis is the most investigated and extensively applied method due to its simplicity, effectiveness, and economic feasibility. A number of operating variables such as temperature, catalyst load, reaction time, and liquid to solid ratio significantly affect the kinetics of hemicellulose hydrolysis. Dilute acid catalyzes hemicellulose fractionation at elevated temperature and pressure within short residence time. This chapter reviews the current literature on hemicellulose hydrolysis methods and identifies the most suitable way to recover maximum hemicellulosic sugars (viz., xylose and arabinose) from LCB.